Financial Development : Structure and Dynamics - de la Torre, Augusto; Feyen, Erik; Ize, Alain (Oxford University Press on behalf of the World Bank, 2015)
This paper analyzes the process of financial development over the last three to four decades from the perspective of the fundamental frictions (agency and collective) to which economic agents were exposed. A comprehensive statistical benchmarking analysis showed that financial development followed regular dynamics that can be largely explained by the underlying frictions. In particular, the sequencing, returns to scale, and shape of the developmental paths for various types of financial activities—including public debt, banking, insurance, asset management, and capital markets—broadly matched benchmark predictions. Reflecting financial innovation and the dynamic interaction between financial and economic development, financial development paths were also found to be strongly dependent on initial conditions. At the same time, policy differences, including the failure to improve the quality of the enabling environment and prevent financial crashes (the dark side of finance), were found to explain a sizable share of the deviations of individual country paths from the benchmarks.